Deadjectival human nouns: conversion, nominal ellipsis, or mixed category? - Sleeman, Petra (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Whereas deadjectival nouns referring to humans such as the Germans have been analyzed as the result of morphological conversion, the human construction the rich in English has been analyzed as a special case of nominal ellipsis. In this paper counterarguments are presented against the ellipsis analysis, mainly focusing on the human construction in Dutch, which has mixed adjectival and nominal properties. Traditionally, deadjectival human nouns ending in the suffix –e are analyzed as the result of morphological derivation. In the ellipsis analysis the suffix –e is analyzed as an inflectional suffix rather than a derivational one, licensing an empty noun. The plural suffix –n and the determiner would provide the human interpretation. In this paper an analysis in the framework of Distributed Morphology is proposed, which is a combination of the ellipsis analysis (without an empty noun) and the traditional derivational/conversion analysis.